2005
DOI: 10.1152/ajpheart.00328.2005
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome degradation of GRK2 during ischemia and ventricular tachyarrhythmias in a canine model of myocardial infarction

Abstract: Arrhythmia-prone subepicardial border zone (EBZ) tissue demonstrates decreased G protein receptor kinase 2 (GRK2) activity and increased sensitivity to isoproterenol 6 -24 h after coronary artery ligation (CAL) in the dog. With the use of a semiquantitative immunofluorescence technique, the relative fluorescence intensity (RF) of GRK2 in EBZ decreased to 24% of that in a remote site (RS) (P Ͻ 0.01, n ϭ 30 cells from 3 dogs), whereas GRK5 RF did not change. Confocal studies of cardiac tissue from transgenic mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 33 publications
(46 reference statements)
3
32
0
Order By: Relevance
“…Additionally, although bortezomib was found to reduce the onset of delayed arrhythmias following coronary ligation in the canine model by upregulating correspondence the adrenergic sensitiser GRK2 (Yu et al, 2005), in the absence of an acute ischaemic event this mechanism may rather be responsible for deleterious cardiac effects (Liu et al, 2005). Indeed, desensitisation of the adrenergic receptor, while preventing tachyarrhythmias (Liu et al, 2005) might potentially favour bradycardia, as accordingly shown in our population.…”
supporting
confidence: 48%
“…Additionally, although bortezomib was found to reduce the onset of delayed arrhythmias following coronary ligation in the canine model by upregulating correspondence the adrenergic sensitiser GRK2 (Yu et al, 2005), in the absence of an acute ischaemic event this mechanism may rather be responsible for deleterious cardiac effects (Liu et al, 2005). Indeed, desensitisation of the adrenergic receptor, while preventing tachyarrhythmias (Liu et al, 2005) might potentially favour bradycardia, as accordingly shown in our population.…”
supporting
confidence: 48%
“…Thus, bortezomib may be applicable to treatment for canine clinical cases with lymphoid malignancies. A previous study showed that 0.2 mg/kg was the maximal tolerated dosage of bortezomib for dogs [21]. And, another study mentioned that 10 ng/ml of bortezomib supplemented to culturing cell lines was nearly corresponding to the clinical dose used in humans [11].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in vivo inhibition of the proteasome by PS-519 and bortezomib was confirmed using whole blood or leukocyte proteasome peptidase activity measurements as a surrogate for their pharmacological efficacy in some studies (67,117,150). Furthermore, the basic arginine/ proline-rich peptide PR-39 has been reported to prevent proteasome-mediated degradation of IB␣ without effects on proteasomal degradation of total cellular protein (10,44).…”
Section: Effects Of Proteasome Inhibitors In the Ischemic And Postiscmentioning
confidence: 96%
“…It should be noted, however, that the majority of these studies did not assess myocardial ATP content or cardiac proteasome activities (10,21,44,67,91,99,116,117,131,150); proteasome inhibitors were employed based on their anti-inflammatory ( (91,146) or to assess whether they affect G protein receptor kinase 2 (GRK2) expression during ischemia (67,150). Nevertheless, in vivo inhibition of the proteasome by PS-519 and bortezomib was confirmed using whole blood or leukocyte proteasome peptidase activity measurements as a surrogate for their pharmacological efficacy in some studies (67,117,150).…”
Section: Effects Of Proteasome Inhibitors In the Ischemic And Postiscmentioning
confidence: 99%